2017
DOI: 10.1080/15548627.2017.1291483
|View full text |Cite
|
Sign up to set email alerts
|

HS1BP3 inhibits autophagy by regulation of PLD1

Abstract: Macroautophagy/autophagy is a membrane trafficking and intracellular degradation process involving the formation of double-membrane autophagosomes and their ultimate fusion with lysosomes. Much is yet to be learned about the regulation of this process, especially at the level of the membranes and lipids involved. We have recently found that the PX domain protein HS1BP3 (HCLS1 binding protein 3) is a negative regulator of autophagosome formation. HS1BP3 depletion increases the formation of LC3-positive autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…PLD1 has been shown to promote cell survival and protect against apoptosis via mediating several signaling pathways 14 . In particular, PLD1 can catalyze phosphatidylcholine (PC) to produce phosphatidic acid (PA), which plays an essential role in autophagy 23 . Accumulative evidence has shown that autophagy is indispensable for kidney proximal tubular cell survival, 24‐26 so the cadmium‐induced cell death and kidney injury in this study may be attributed, at least partially, to the impaired autophagy resulted from PLD1 downregulation, but further experiment is needed to testify it.…”
Section: Discussionmentioning
confidence: 99%
“…PLD1 has been shown to promote cell survival and protect against apoptosis via mediating several signaling pathways 14 . In particular, PLD1 can catalyze phosphatidylcholine (PC) to produce phosphatidic acid (PA), which plays an essential role in autophagy 23 . Accumulative evidence has shown that autophagy is indispensable for kidney proximal tubular cell survival, 24‐26 so the cadmium‐induced cell death and kidney injury in this study may be attributed, at least partially, to the impaired autophagy resulted from PLD1 downregulation, but further experiment is needed to testify it.…”
Section: Discussionmentioning
confidence: 99%
“…More elaborate studies using proximity ligation assay will be required to quantify further the importance and relevance of this association from a therapeutic point of view. Since PLD1 levels were elevated in the astrocytic and mitochondrial compartments in the previously reported study, our future studies will explore mechanisms in which PLD1 has been implicated and plays an important role in the progression of neurodegenerative states including autophagy [ 29 , 94 , 95 , 96 ], neuroinflammation [ 35 , 64 , 97 , 98 , 99 , 100 , 101 , 102 ], reactive oxygen species [ 103 , 104 , 105 , 106 ] and infection [ 35 , 107 , 108 , 109 ] and how these contribute to the synaptic dysfunction leading to cognitive decline in our studies.…”
Section: Discussionmentioning
confidence: 97%
“…PLD1 can hydrolyse major membrane glycerophospholipids to the lipid second messenger PA, which plays a role in disease processes such as cancer 11 . PLD1 and its product, PA, participate in various physiological and pathological processes, such as cell growth, invasion, metabolism and autophagy 10,12,13 . PLD1 exhibits a higher expression level in colorectal tumours, bladder cancer and breast cancer 14–16 .…”
Section: Discussionmentioning
confidence: 99%
“…11 PLD1 and its product, PA, participate in various physiological and pathological processes, such as cell growth, invasion, metabolism and autophagy. 10,12,13 PLD1 exhibits a higher expression level in colorectal tumours, bladder cancer and breast cancer. [14][15][16] The high expression of PLD1 in tumour tissues is related to a poor prognosis in patients with colorectal cancer and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%